Perkembangan Ekonomi Pariwisata di Kawasan Danau Toba Tahun 2022 - Manik, Gres Br.; Fitriyah, Disti; saragih, Bryan samwel; surbakti, Dedy; Purba, Mutiara Nur Umairoh (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The purpose of this study was to determine the determinants of economic growth in the districts around Lake Toba. The research method used is a qualitative method through interviews, surveys and direct questions and answers. The data used are secondary data and the data period is from 2018 to 2022 in the Lake Toba area. The results of this study are that Government Expenditure, infrastructure, Capital Expenditure Allocation and Tourism have an overall positive impact on Economic Growth in the Lake Toba Area. The number of Tourist Visits and road infrastructure have an impact on the development of Lake Toba as a tourism business that has increased, such as in the Hotel and Restaurant sectors. In developing the tourism potential of Lake Toba, the greatest strengths are natural tourism, artificial tourism, and also cultural tourism. The weaknesses are human resources, facilities and infrastructure that still need to be improved, and limited capital. For this reason, good cooperation is needed between the government and the local community so that the development of the tourism business in the Lake Toba Area can be improved even better so that the economy can develop well.